2022
DOI: 10.3389/fnut.2022.965654
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids in preterm human milk

Abstract: BackgroundGlucocorticoids (GCs), cortisol and cortisone, are essential regulators of many physiological responses, including immunity, stress and mammary gland function. GCs are present in human milk (HM), but whether maternal and infant factors are associated with HM GC concentration following preterm birth is unclear.Materials and methodsHM samples were collected on postnatal day 5 and 10 and at 4 months’ corrected age (4m CA) in a cohort of moderate- and late-preterm infants. GCs in HM were measured by liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 62 publications
1
1
1
Order By: Relevance
“…Other studies have found that HM cortisol concentrations are highest in the colostral phase and decrease in mature milk after term birth ( 44 , 45 ). This finding contrasts with the studies of preterm milk over time, which show higher cortisol levels compared to term milk ( 46 , 47 ), with levels increasing over time ( 47 ). These conflicting reports may represent differences in cortisol secretion in term vs. preterm milk and have differing impacts on the recipient infant.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Other studies have found that HM cortisol concentrations are highest in the colostral phase and decrease in mature milk after term birth ( 44 , 45 ). This finding contrasts with the studies of preterm milk over time, which show higher cortisol levels compared to term milk ( 46 , 47 ), with levels increasing over time ( 47 ). These conflicting reports may represent differences in cortisol secretion in term vs. preterm milk and have differing impacts on the recipient infant.…”
Section: Discussioncontrasting
confidence: 99%
“…These conflicting reports may represent differences in cortisol secretion in term vs. preterm milk and have differing impacts on the recipient infant. The concentrations of HM cortisol detected in our study (collected from a full-breast expression) were comparable to those reported in other preterm milk studies and lower than those reported in studies that collected hindmilk samples ( 42 , 47 , 48 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation